2021
DOI: 10.1111/bph.15352
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphoproteomic identification of vasopressin‐regulated protein kinases in collecting duct cells

Abstract: Background and Purpose The peptide hormone vasopressin regulates water transport in the renal collecting duct largely via the V2 receptor, which triggers a cAMP‐mediated activation of a PKA‐dependent signalling network. The protein kinases downstream from PKA have not been fully identified or mapped to regulated phosphoproteins. Experimental Approach We carried out systems‐level analysis of large‐scale phosphoproteomic data quantifying vasopressin‐induced changes in phosphorylation in aquaporin‐2‐expressing cu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…2 ). Seven of the 66 decreasing phosphosites had basic amino acids in positions + 5 and + 6 (as previously seen [ 21 ]) (Group I.A.1). The remaining 59 decreasing phosphosites (Group I.A.2) were partitioned into three groups based on their time-course pattern.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…2 ). Seven of the 66 decreasing phosphosites had basic amino acids in positions + 5 and + 6 (as previously seen [ 21 ]) (Group I.A.1). The remaining 59 decreasing phosphosites (Group I.A.2) were partitioned into three groups based on their time-course pattern.…”
Section: Resultssupporting
confidence: 76%
“…The V2R is a G-protein coupled receptor (GPCR) that signals through the heterotrimeric G-protein alpha subunit (G α s) to activate adenylyl cyclase type 6 [ 17 , 18 ] and increase cyclic adenosine monophosphate (cAMP) levels [ 19 ] in collecting duct cells. Protein kinase A (PKA) appears to be the main cAMP effector in the collecting duct, mediating altered phosphorylation of multiple proteins [ 20 ], many of which are themselves protein kinases that phosphorylate their own sets of substrates [ 21 ]. One major target of PKA is AQP2 [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In quantitative phosphoproteomic analyses, AAK1 was shown to be phosphorylated upon V2R activation in renal collecting duct cells [ 48 , 49 ]. However, its inhibition by our AURKA inhibitors is unlikely because inhibition of clathrin-mediated endocytosis in renal principal cells causes an accumulation of AQP2 in the plasma membrane [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…They could potentially constitute additional components of the machinery controlling AQP2 in renal principal cells. Phosphoproteomic studies revealed an AVP/V2R-dependent signaling network in renal-collecting duct cells that involves the regulation of a plethora of kinases, partly in a PKA-independent manner [ 48 , 49 , 81 ]. We had previously identified 19 potential regulators of the AQP2 redistribution via siRNA-mediated knockdown of 719 kinase-related genes, one of which was AURKA [ 34 ].…”
Section: Discussionmentioning
confidence: 99%